Pengaruh Komunikasi dan Peran Dosen Penasehat Akademik Terhadap Prestasi Akademik Mahasiswa Pada Program Studi Manajemen Administrasi Politeknik Belitung - Venny Resti Fachlovi (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
Academic advisory lecturers have an essential role in encouraging student success in attending lectures. For this reason, academic advisory lecturers tasked with guiding students must prepare themselves as well as possible to optimize their role as academic advisors. This research is quantitative descriptive. The variables in this study are 2 independent variables: the communication variable and the role of the Academic Advisor lecturer, and the dependent variable is the student's academic achievement. The sample in this study was 37 second-semester students of the Administrative Management Study Program. Data collection techniques using a questionnaire. Based on the study results, the communication variable has a positive and significant effect on student academic achievement. It is shown in hypothesis testing based on the results of the T-test (partial), showing that the communication variable (X1) T-count > T-table (7.580 > 2.032) and significance < 0.05 (0.000 < 0.05), which means that Ho is rejected. Ha is accepted. The PA lecturer variable has a positive and significant effect on student academic achievement. It is shown in hypothesis testing seen from the results of the T-test (Partial) showing that the role of the PA lecturer (X2) T-count > T-table (3.619 > 2.032) and a significance < 0.05 (0.001 < 0.05), which means that the the the Ho is rejected and Ha accepted. Communication variables and PA lecturers positively and significantly affect student academic achievement. It is shown in the results of hypothesis testing based on the results of the F test showing that the F-count obtained is 80.371 with a significance of 0.000, and the value of the F-table is 3.267. If the results of F-count with F-table are compared, then F-count > F-table (80.371 > 3,267) and significance < 0.05 (0.000 < 0.05). These results indicate that Ho is rejected and Ha is accepted, which means that there is a jointly significant influence between the communication variable (X1) and the PA lecturer role variable (X2) on student academic achievement (Y). The suggestion from the results of this study is that PA lecturers should communicate more intensely to their guidance students by motivating students. It can further increase the educational value of the students under his guidance. And students must be more active in communicating with their respective PA lecturers and do not hesitate to PA lecturers to consult if there are problems encountered in lectures.